Dpp represses eagle expression at short-range, but can repress its expression at a long-range via EGFR signal repression. - Kim, S.Y.; Jung, K.I.; Kim, S.H.; Jeon, S.H. (Molecules and Cells, 2008)
Nervous system development takes place after positional information has been established along the dorsal-ventral (D/V) axis. The initial subdivision provided by a gradient of nuclear dorsal protein is maintained by the zygotic genes expressed along the D/V axis. In this study, an investigation was conducted to determine the range of Dpp function in repressing the expression of eagle (eg) that is present in intermediate neuroblasts defective (ind) and muscle specific homeobox (msh) gene domain. eg is expressed in neuroblast (NB) 2-4, 3-3 and 6-4 of the msh domain, and NB7-3 of the ind domain at the embryonic stage 11. In decapentaplegic (dpp) loss-of-function mutant embryos, eg was ectopically expressed in the dorsal region, while in dpp gain-of-function mutants produced by sog or sca-GAL4/UAS-dpp, eg was repressed by Dpp. It is worthy of note that Dpp produced from sim;;dpp embryos showed that Dpp could function at long range. However, Dpp produced from en-GAL4/UAS-dpp or wg-GAL4/UAS-dpp primarily acted at short-range. This result demonstrated that this discrepancy seems to be due to the repression of Dpp to EGFR signaling in sim;;dpp embryos. Taken together, these results suggest that Dpp signaling works at short-range, but can function indirectly at long-range by way of repression of EGFR signaling during embryonic neurogenesis.